Heart transplantation in high-risk recipients employing donor marginal grafts preserved with ex-vivo perfusion - Sponga, Sandro; Vendramin, Igor; Salman, Jawad; Ferrara, Veronica; De Manna, Nunzio Davide; Lechiancole, Andrea; Warnecke, Gregor; Dralov, Andriy; Haverich, Axel; Ius, Fabio; Bortolotti, Uberto; Livi, Ugolino; et al. (Transplant international, 2023)
Extending selection criteria to face donor organ shortage in heart transplantation (HTx) may increase the risk of mortality. Ex-vivo normothermic perfusion (EVP) limits ischemic time al-lowing assessment of graft function. We investigated the outcome of HTx in 80 high-risk recipients transplanted with marginal donor and EVP-preserved grafts, from 2016 to 2021. The recipients median age was 57 years (range, 13-75), with chronic renal failure in 61%, impaired liver function in 11% and previous cardiac surgery in 90%; 80% were mechanically supported. Median RADIAL score was 3. Mean graft ischemic time was 118±25 minutes, “out-of-body” time 420±66 minutes and median cardiopulmonary bypass (CPB) time 228 minutes (126-416). In-hospital mortality was 11% and ≥moderate primary graft dysfunction 16%. At univariable analysis, CPB time and high central venous pressure were risk factors for mortality. Actuarial survival at 1 and 3 years was 83±4%, and 72±7%, with a median follow-up of 16 months (range 2-43). Recipient and donor ages, pre-HTx extracorporeal life support and in-tra-aortic balloon pump were risk factors for late mortality. In conclusion, the use of EVP allows extension of the graft pool by recruitment of marginal donors to successfully perform HTx even in in high-risk recipients.